Bioinspired multifunctional layered magnetic hybrid materials. Issue 1 (1st February 2019) - Debus, Christian; Wu, Baohu; Kollmann, Tina; Duchstein, Patrick; Siglreitmeier, Maria; Herrera, Steven; Benke, Dominik; Kisailus, David; Schwahn, Dietmar; Pipich, Vitaliy; Faivre, Damien; Zahn, Dirk; et al.
Abstract : Nature has taken millennia to come up with unique solutions for providing materials with properties tailored toward versatile demands, making use of the very limited resources available in natural environments. Today, these biomaterials can be used as inspiration by combining and 'remixing' the concepts that nature displays to create new bioinspired materials. Here, the authors present materials combining the structural and functional elements of multiple biominerals: the inorganic–organic lamellar structure responsible for the high fracture toughness of nacre; highly mineralized composites, which give different mollusk teeth their very high hardness and strength; and the particle orientation and magnetic anisotropy of magnetosomes, giving magnetotactic bacteria a sensitive means to navigate along geomagnetic field lines. The authors show how the mechanical properties of a composite material can be improved with the addition of each of these elements. Small-angle neutron scattering studies and molecular simulation give additional insights into the mineralization from the very first attached ions to the finished composite.